Chiari malformation type 1 presenting as unilateral progressive foot drop: a case report and review of literature - Chamara Jayamanne; Lakkumar Fernando; Sachith Mettananda (BMC, 2018)
Abstract Background Foot drop is a disabling clinical condition with multiplicity of causes, which requires detailed evaluation to identify the exact aetiology. Here, we report an extremely rare cause of foot drop in a child, which if not recognized early, could lead to multiple complications. Case presentation A 6-year-old girl presented with difficulty in walking and left sided foot droop for1-month duration. On examination she had reduced muscle power in dorsiflexors and plantar flexors and diminished knee and absent ankle jerk in the left side. Sensory loss was noted in L4 and L5 dermatomes on the left side. Superficial abdominal reflex was absent on the left side while preserved in the right. Nerve conduction and electromyography revealed nerve root or spinal cord cause for the foot drop. These results prompted ordering MRI spine and brain which revealed Chiari malformation type-1 with holocord syrinx extending from the cervicomedullary junction to conus medullaris. Conclusions This case highlights the importance of considering broad differential diagnosis for foot drop and value of the complete neurological examination including superficial reflexes in arriving at a diagnosis. Prompt diagnosis helped to early neurosurgical referral and intervention which is an important prognostic factor.